2011
DOI: 10.3389/fpsyg.2011.00124
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Music Program on Phonological Awareness in Preschoolers

Abstract: The present experiment investigated the effect of a music program on phonological awareness in preschoolers. In particular, the effects of a music program and a phonological skills program on phonological awareness were compared. If language and music share basic processing mechanisms, the effect of both programs on enhancing phonological awareness should be similar. Forty-one preschoolers (22 boys) were randomly assigned to a phonological skills program, a music program, and a control group that received spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
211
4
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(264 citation statements)
references
References 17 publications
22
211
4
7
Order By: Relevance
“…Indeed, music training is associated with L1 phonological perception (Zuk et al, 2013) and reading abilities (Corrigall & Trainor, 2011), and with L2 fluency (Swaminathan & Gopinath, 2013;Yang, Ma, Gong, Hu, & Yao, 2014). Longitudinal interventions with random assignment indicate that music training may actually cause improvement in children's speech perception (Degé & Schwarzer, 2011;Flaugnacco et al, 2015;François, Chobert, Besson, & Schön, 2013;Moreno et al, 2009;Thomson et al, 2013).…”
Section: Music Training and Speech Perceptionmentioning
confidence: 99%
“…Indeed, music training is associated with L1 phonological perception (Zuk et al, 2013) and reading abilities (Corrigall & Trainor, 2011), and with L2 fluency (Swaminathan & Gopinath, 2013;Yang, Ma, Gong, Hu, & Yao, 2014). Longitudinal interventions with random assignment indicate that music training may actually cause improvement in children's speech perception (Degé & Schwarzer, 2011;Flaugnacco et al, 2015;François, Chobert, Besson, & Schön, 2013;Moreno et al, 2009;Thomson et al, 2013).…”
Section: Music Training and Speech Perceptionmentioning
confidence: 99%
“…Both activities were part of the high school curriculum, which was otherwise identical for both groups. We also tested students' language skills (phonological memory, phonological awareness, and rapid naming ability) to determine whether in-school music engendered benefits for literacy skills, a prediction consistent with cross-sectional studies (39)(40)(41)(42)(43)(44)(45). The two groups were matched demographically and on all outcome measures at the start of the study (see Table S1 for demographic information for the two groups).…”
Section: Significancementioning
confidence: 99%
“…Studies comparing nonmusicians with musicians who began training early in life have revealed a "signature" set of enhancements associated with musical experience (27,28). Relative to nonmusician peers, musicians tend to show enhanced speech-innoise perception (29)(30)(31)(32)(33)(34), verbal memory (30)(31)(32)(33)(35)(36)(37)(38), phonological skills (39)(40)(41)(42)(43)(44)(45), and reading (46-50), although not without exception (51,52). Music training has also been linked to enhancements in the encoding of sound throughout the auditory system.…”
mentioning
confidence: 99%
“…The rhythmic structure of music and language are aligned when we sing, and therefore children who are perfectly "in phase" when singing should also be those children who entrain more accurately and who develop better phonological skills. This prediction about music was supported by a recent study by Dege and Schwarzer (2011), who provided musical training to young German children (5-year-olds). They demonstrated a positive effect of training on the children's phonological awareness of syllables and rhymes.…”
Section: Metrical Structure Phonology and Musicmentioning
confidence: 52%